2010
DOI: 10.5433/1679-0359.2010v31n1p75
|View full text |Cite
|
Sign up to set email alerts
|

Fenologia de espécies nativas com potencial paisagístico

Abstract: ResumoO presente estudo visou determinar a fenologia de 10 espécies oriundas do ecossistema de Campos no estado do Paraná. AbstractThe aim of this work was to study the phenology of ten species that occur in the "Campos" ecosystem in Paraná state. The meteorological variables that had been related with the phenology were: air temperature, relative humidity, precipitation and photoperiod. The results show that 80% of the species present ending of the period of budding between April and May. Cuphea calophylla w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
1
3
0
5
Order By: Relevance
“…In phenological studies in Campo areas in Paraná, conducted by Martini et al (2010), similar results were found with the species Tibouchina gracilis, where short flowering periods and long periods of leaf production stagnation were presented, less relevant characteristics. Tibouchina gracilis remains for four months in the flowering phase, seven months in the flowering phase stagnation of leaf production and even a long period of desiccation.…”
Section: Tibouchina Dubia (Manacá-serrano)supporting
confidence: 65%
“…In phenological studies in Campo areas in Paraná, conducted by Martini et al (2010), similar results were found with the species Tibouchina gracilis, where short flowering periods and long periods of leaf production stagnation were presented, less relevant characteristics. Tibouchina gracilis remains for four months in the flowering phase, seven months in the flowering phase stagnation of leaf production and even a long period of desiccation.…”
Section: Tibouchina Dubia (Manacá-serrano)supporting
confidence: 65%
“…As the species in question presented higher concentrations of leaf chlorophyll, physiologically, it has a great capacity of photosynthesizing carbohydrates (GUERTAL and FRANCK, 2012), and this possibly made its development faster and reflected in a greater number of flowers. However, because they belong to different species, the phenology of the herbaceous plants is distinct, and may differ in the flowering of each plant (MARTINI et al, 2010), as evidenced in the present work.…”
Section: Resultsmentioning
confidence: 62%
“…Trabalhos como os de Tognon e Cuquel (2016), Heiden et al (2006Heiden et al ( , 2007, Martini et al (2010), Leal e Biondi (2006) e Machado et al (2006), que realizaram prospecções de espécies nativas com potencial ornamental, destacaram a viabilidade do cultivo de espécies nativas de diversos hábitos, principalmente arbóreas, para compor a arborização de cidades, jardins urbanos e outras áreas verdes como alternativas às exóticas amplamente cultivadas. O cultivo de espécies nativas com potencial econômico vai além das plantas ornamentais, mas a associação de características ornamentais aos aspectos agrícola, ecológico, genético, social, econômico, científico, educacional, cultural, recreativo e estético permite a conservação e valorização da biodiversidade brasileira (Coradin et al, 2011;BFG, 2015;Vieira et al, 2018;Coradin et al, 2018), além de integrar essas áreas na paisagem regional de forma a garantir uma maior harmonização ambiental na matriz urbano-rural das cidades brasileiras.…”
Section: Espécies Nativas Com Potencial Ornamental Ocorrentes Na Mata Busca Vidaunclassified